'Proper football people': Talking soccer on Sky Sports News. (March 2016) - Tolson, Andrew
Abstract: This paper examines a television programme with a paradoxical communicative structure. It is a sports programme that provides live updates and some commentary on football matches which viewers, for contractual reasons, cannot see. Accordingly, the void created by this paradoxical situation has to be filled by talk; but unlike radio, because this is a TV programme, the viewer is watching the talkers. The paper looks at two types of talk produced in this context: firstly forms of debate and argument (which like other types of sports talk have a 'sociable' emphasis); and secondly the subgenres of reports, commentary and updates, especially where these involve an element of narrative 'retelling'. The whole programme culminates in a classified reading of the day׳s football results, which in the UK, has become a weekly ritual of broadcast talk. Highlights: Analysis of a TV sports programme with a paradoxical televisual structure. Examination of forms of talk produced in this context: sociable argument, report and commentary. A hybrid form of broadcasting with a distinctive 'communicative ethos'. Evidence of the use of the 'present-perfect' tense in narrative re-telling.